Morphological transition of eutectic NiAl3 phase in Al–Mg2Si cast alloys. (10th December 2017) - Xue-xin, Meng; Chong, Li; Xiang-fa, Liu; Yong-chang, Liu; Li-ming, Yu; Hui-jun, Li
ABSTRACT: Two- and three-dimensional morphological features of eutectic NiAl3 in Al–Mg2 Si were studied in detail. It is found that eutectic NiAl3 transforms from enormous irregular shapes to fine regular rods, and the transition is related to (Al+Mg2 Si) binary eutectic during the process of eutectic structural evolution. The explanation about the morphological change was discussed and analyzed in terms of the detailed microstructural observation of nucleation and growth patterns.